The evaluation of the bilateral investment treaty (BIT) between Jordan and China (reality and ambition) - Albraizat, Hamza Madallah; Jiang, Zuoli (Journal of Economic, Administrative and Legal Sciences, 2020)
Jordan has signed more than 54 bilateral agreements to encourage investment and due to the economic and legal importance of increasing the volume of investment between China and Jordan, we found that study because of one of these agreements most important of them the huge investment volume that Jordan witnessed, as the size of Chinese investment in the last three years reached over four billion USD s. China was became one of the largest foreign countries investing in Jordan also rapid development in trade relations on the other hand seemed important for research to contribute to enriching knowledge for those and planners in the policy- making for trade Foreign and promote trade with China as the second most powerful economy in the world also a lack of studies and research related to the theme of Jordan China trade agreement and work to enrich the research subject and study the economic and legal significance.As the bilateral relationship started with the bilateral investment treaty that took place between Jordan and China in 2001, it was extended for ten years, and work will end in year 2021.Because of the limited space that we must write cover the main points, which are highlights of the articles of the agreement and explain the essential matters related to legal and economic regulation. The parties to the dispute, the arbitration agreement, the challenges of the arbitrators, and their isolation, the representation of the parties, the "provisional attachment, " the language and procedures of the arbitration, "the issuance of the arbitration decision and its implementation.
Keywords: investment treaty; Jordan; China; investment promotion; international arbitration